Retracted: Maternal outcome of term obstetric emergencies referred to tertiary care centre - Badal, Shivani; Singh, L. Ranjit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The article "Maternal outcome of term obstetric emergencies referred to tertiary care centre" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Reproduction, Contraception, Obstetrics and Gynecology. The article is retracted due to error in data informed by corresponding author.